The lower bound of nonlocal gradient for non-convex and non-smooth image patches based regularization. (1st March 2022) - Meng, Junying; Wang, Faqiang; Cui, Li; Liu, Jun
Abstract: In the inverse problem of image processing, we have witnessed that the non-convex and non-smooth regularizers can produce clearer image edges than convex ones such as total variation (TV). This fact can be explained by the uniform lower bound theory of the local gradient in non-convex and non-smooth regularization. In recent years, although it has been numerically shown that the nonlocal regularizers of various image patches based nonlocal methods can recover image textures well, we still desire a theoretical interpretation. To this end, we propose a non-convex non-smooth and block nonlocal regularization model based on image patches. By integrating the advantages of the non-convex and non-smooth potential function in the regularization term, the uniform lower bound theory of the image patches based nonlocal gradient is given. This approach partially explains why the proposed method can produce clearer image textures and edges. Compared to some classical regularization methods, such as TV, non-convex and non-smooth regularization, nonlocal total variation and block nonlocal total variation, our experimental results show that the proposed method improves restoration quality.